On Algebraic Basis of the Algebra of Symmetric Polynomials on lp(Cn) - Victoriia Kravtsiv; Taras Vasylyshyn; Andriy Zagorodnyuk (Journal of Function Spaces)
We consider polynomials on spaces lpCn,1≤p<+∞, of p-summing sequences of n-dimensional complex vectors, which are symmetric with respect to permutations of elements of the sequences, and describe algebraic bases of algebras of continuous symmetric polynomials on lpCn.